2008
DOI: 10.1007/s00534-008-1328-8
|View full text |Cite
|
Sign up to set email alerts
|

A simple and safe pancreas transection using a stapling device for a distal pancreatectomy

Abstract: Pancreatic fistula is the most common major complication to occur after distal pancreatectomy, ranging in frequency from 5% to 40%. The appropriate technique for treating the pancreatic stump still remains controversial. Thirty-six patients underwent distal pancreatectomy in Kagawa University Hospital between January 2000 and February 2007. Their hospital records were reviewed to evaluate the usefulness of a stapling closure using several types of staplers in comparison to a suture closure. They were subdivide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…Okano et al [15] noted that the most important and technically difficult step of a stapler dissection was to prevent the pancreatic tissue from tearing during compression. Therefore, they clamped the stapler jaw carefully and slowly over more than 5 min at a fixed speed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okano et al [15] noted that the most important and technically difficult step of a stapler dissection was to prevent the pancreatic tissue from tearing during compression. Therefore, they clamped the stapler jaw carefully and slowly over more than 5 min at a fixed speed.…”
Section: Discussionmentioning
confidence: 99%
“…During the 2nd period, the pancreas was transected using the echelon 60 linear stapler (Ethicon Endo-Surgery; Johnson & Johnson, Tokyo, Japan). The closure jaw was clamped carefully and slowly, taking more than 5 min at a fixed speed [15]. All patients underwent a splenectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there has been a trend towards favoring stapler closure rather than hand-sewn closure for the pancreas. Various stapling devices are available for use in pancreatic surgery to divide the pancreatic parenchyma, and their convenience and usefulness have been reported [5,6,7,8]. However, the incidence of PF after DP with the use of stapling devices is varied, being reported to range from 5 to 60% [1,9,10,11,12,13,14], and the risk factors for PF as well as the criterion for stapler selection are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The use of stapling devices has achieved widespread application in gastro-intestinal and hepatopancreatobiliary surgery and has led to greatly reduced operative times and standardization of techniques [19,20]. In particular, in pancreatic surgery the use of the stapler in distal pancreatectomy has been reported extensively in the literature [6,7,8,9,10,11]. However, only a few papers describe the use of the stapler for the division of the uncinate process during performance of a PD [12,13,14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, several techniques have been employed to simplify and reduce bleeding during this part of the operation including the use of a saline-linked radio frequency device [4,5]. While a number of studies have described the use of surgical staplers in distal pancreatectomy and division of the neck of the pancreas during a PD [6,7,8,9,10,11] specifically, only a few studies have described the utility of stapling devices in division of the uncinate process during PD [12,13,14,15,16]. Most studies are technique papers and do not provide the peri-operative outcomes and morbidity data; some concluded that generating objective peri-operative data was the next step in evaluating the technique they described.…”
Section: Introductionmentioning
confidence: 99%